2009
DOI: 10.1590/s0102-311x2009000700007
|View full text |Cite
|
Sign up to set email alerts
|

Exploração de fatores de risco para câncer de mama em mulheres de etnia Kaingáng, Terra Indígena Faxinal, Paraná, Brasil, 2008

Abstract: O objetivo do presente estudo foi analisar a saúde das mulheres Kaingáng da Terra Indígena Faxinal, Paraná, Brasil, quanto aos fatores de risco para o câncer de mama. O estudo, de caráter descritivo-exploratório, foi realizado com 95,4% da população feminina com vinte anos ou mais. O aleitamento materno por mais de 1 ano foi relatado por 92,3% das mulheres; 41,4% tinham mais de cinco filhos; a idade média da menarca foi 13,4 anos; 61,5% nunca tinham ouvido falar do câncer de mama; o auto-exame da mama era real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 7 publications
0
3
0
18
Order By: Relevance
“…[1012] This study found a higher prevalence of married women in both groups, 65.21%, and 52.17% respectively. In both groups, women had income up to the minimum monthly salary.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…[1012] This study found a higher prevalence of married women in both groups, 65.21%, and 52.17% respectively. In both groups, women had income up to the minimum monthly salary.…”
Section: Discussionmentioning
confidence: 72%
“…Some studies conducted in the unified health system hospitals in Brazil, has related low family income as a risk factor for BC mainly in cases of late diagnoses. [11213]…”
Section: Discussionmentioning
confidence: 99%
“…No estudo de Pinho e Coutinho (2007), mais da metade das mulheres da amostra era sedentária, e, dentre as que praticavam exercícios físicos regulares, a caminhada também foi o mais frequente. Silva et al (2009), ao explorarem a presença de fatores de risco para câncer de mama em mulheres indígenas no Paraná, verificou que apenas 17,3% praticavam exercícios pelo menos três vezes na semana regularmente. A atividade física parece exercer efeitos nos níveis hormonais e, dessa maneira, pode diminuir o risco de câncer de mama.…”
Section: Discussionunclassified
“…11 These data concern do reflect, as health professionals, including nurses, are working on the issues of health education in basic unit of reference to which they belong and how are being carried out the actions of promotion and prevention in the context of women's health.…”
Section: Type Of Search Descriptive-exploratorymentioning
confidence: 99%